The causal relationship between smoking, alcohol consumption, and renal clear cell carcinoma: a Mendelian randomization study - Cui, Hongbin; Du, Junji; Xue, Hongbo; Zhao, Yingjian; Li, Chengwen (Frontiers in Genetics, 2024)
Observational studies have found a correlation between the consumption of tobacco and alcohol and the likelihood of developing renal cell carcinoma. To establish if these connections indicate causal relationships, we performed an MR analysis using a two-sample Mendelian randomization (MR) approach. For the number of daily cigarettes, lifetime smoking index, smoking initiation, and weekly drinking, we employed 44, 108, 174, and 76 single nucleotide polymorphisms (SNPs) as instrumental variables. The outcome data were obtained from FinnGen Alliance, which included a combined total of 429,290 individuals, comprising both men and women. The likelihood of starting smoking is genetically influenced and has a direct association with the chances of developing renal cell carcinoma. For each standard deviation increase in the number of smoking initiation, there is a 1.55 odds ratio (95% CI: 1.04-2.33; P = 0.03). However, no causal relationship was found between daily cigarette consumption and lifetime smoking index with the risk of renal cell cancer. Individuals with a genetic predisposition for weekly alcohol consumption showed a reduced risk of renal cell cancer, with an odds ratio (OR) of 0.45 (95% CI: 0.26-0.81; P=0.007) for each standard deviation increase in the number of drinks per week. The MR analysis was conducted using the inverse-variance weighted (IVW) method to estimate causal effects. To address potential violations of MR assumptions due to directional pleiotropy, we performed MR-Egger regression and MR-PRESSO (Mendelian Randomization Pleiotropy RESidual Sum and Outlier) analysis. MR-Egger regression was used to detect and adjust for directional pleiotropy, indicated by a non-zero intercept. MR-PRESSO was applied to identify and correct for potential outlier SNPs that might bias the causal estimates. These methods help ensure that the causal inferences drawn are robust and not significantly influenced by pleiotropic effects. Based on the available evidence, our study implies a potential causal relationship between alcohol consumption and renal cell cancer, while no such association was observed with smoking.